Current state and trends of the use of vegetable feedstock in aquaculture feeds (review) - V. I. Pakhomov; V. F. Khlystunov; S. V. Braginets; O. N. Bakhchevnikov (Аграрная наука Евро-Северо-Востока)
Rising prices of traditional feedstock for feed preparation (fish meal and oil) is a problem for aquaculture enterprises. Their replacement with inexpensive components of vegetable origin is the way for solving the problem. The aim of the study is to generalize and analyze scientific data on using new types of vegetable feedstock in aquaculture feeds, on technologies of their preparation and use, influence on feed quality. Selection and systematic review of scientific literature on the topic of the study for the period of 2017-2022 has been carried out. The derivatives of land agricultural plant products such as oilseed meal, protein concentrates, gluten and food industry wastes are the main types of vegetable feedstock for feed preparation in aquaculture. Currently, vegetable oils are the best variants for replacing fish oil in fish diets. Partial or complete replacement of fishmeal and oil with new types of vegetable feedstock is possible and does not lead to deterioration of fish health and growth rate when these components are included in the diet at recommended doses. Such a replacement is economically advantageous. But there are negative effects in the use of vegetable feedstock, such as the presence of anti-nutritional factors that limit its use in aquaculture. The development of recipes of cost-effective fish feeds in which fish meal and oil are completely replaced by vegetable components is a research priority for the development of intensive aquaculture.